2019
DOI: 10.1021/acs.iecr.9b00168
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Observation of Hydrate Phase Transition in Porous Medium via Microfluidic Application

Abstract: The gas–liquid–solid phase transition of hydrates is complex and has effects that are coupled with the heat-mass transfer in reservoirs; thus, this phase transition is related to the determination of flow assurance and production efficiency. The microfluidic technology applied in this research can simulate a porous medium and is an alternative to the conventional sand-packing approach, encompassing real characteristics of interfaces between multiple phases, reducing the randomness of pore shape, and mastering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 32 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…As for the pore-scale experimental studies, the microfluidic technique [25][26][27][28][29] and microscopic X-ray computed tomography (micro-CT) [30][31][32][33] have been widely used to observe the hydrate distribution behaviors within the porous media from the perspective of 2-D and 3-D. Besides the morphological observation, several experimental attempts have also been conducted to investigate the physical and chemical mechanisms during the hydrate dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…As for the pore-scale experimental studies, the microfluidic technique [25][26][27][28][29] and microscopic X-ray computed tomography (micro-CT) [30][31][32][33] have been widely used to observe the hydrate distribution behaviors within the porous media from the perspective of 2-D and 3-D. Besides the morphological observation, several experimental attempts have also been conducted to investigate the physical and chemical mechanisms during the hydrate dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…Research into methane hydrate dissociation spans multiple scales, 13, [23][24][25] with pore-scale 26,27 studies offering detailed insights into the sediment porous media. Techniques like microfluidic observations [28][29][30][31] and micro-CT imaging [32][33][34][35][36] have been instrumental in visualizing the dynamic evolution of hydrate pore habits. These studies have revealed consistent patterns in hydrate dissociation, such as the gradual shrinkage of hydrate clusters and the transition of surface shapes, influenced by mass and heat transfer limitations.…”
Section: Introductionmentioning
confidence: 99%